2003
DOI: 10.1046/j.1537-2995.2003.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

An improved serodiagnostic test for Chagas' disease employing a mixture of Trypanosoma cruzi recombinant antigens

Abstract: The combination of three T. cruzi recombinant antigens in a multiantigen immunoassay was highly sensitive and specific for Chagas' disease diagnosis. It is proposed that it can be applicable in blood bank screening in conjunction with the conventional serologic tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 27 publications
6
80
0
4
Order By: Relevance
“…As has already been shown, this approach proved to be successful, with improvement of Sp and Se. 13,15,16 Herein, both tests were found to display 99.5% Se. Similar results were obtained by Peralta and others, 14 who showed that recombinant antigens were 91-93% sensitive.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…As has already been shown, this approach proved to be successful, with improvement of Sp and Se. 13,15,16 Herein, both tests were found to display 99.5% Se. Similar results were obtained by Peralta and others, 14 who showed that recombinant antigens were 91-93% sensitive.…”
Section: Discussionmentioning
confidence: 79%
“…Other preparations use recombinant proteins or a collection of short recombinant peptides containing specific T. cruzi epitopes, increasing the Sp of the assays. [14][15][16] More recently, chimeric recombinant proteins designed with selected amino acid sequences increased the Se and Sp in diagnostic assays. 17,18 In this scenario, because of the heterogeneity of the performance reported by the tests for Chagas disease diagnosis, we decided to assess the reported quality of four EIA tests for their ability to specifically detect T. cruzi antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a rapid immunochromatographic assay (Chagas Stat-Pak) was developed employing a mixture of T. cruzi recombinant antigens (Umezawa et al, 1999 and2003). This test allows the reaction to be viewed by naked eye against a background that is almost white.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the performance of each recombinant antigen (sensitivity and specificity values), three recombinant antigens were combined in a single ELISA resulting in a multi-antigen test that was very sensitive and specific for the diagnosis of Chagas' disease (Umezawa et al, 2003). Based on these results, a novel immunochromatography assay (Chagas Stat-Pak) for diagnosis of Chagas' disease was developed by combining relevant T. cruzi antigens.…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available ELISA have been evaluated for accuracy in the diagnosis of Chagas disease. Most of the commercial serologic tests employ epimastigote antigens and show a high number of inconclusive and false-positive results, with high economic and social costs (Umezawa et al 2003). Some ELISA kits show up to 100% sensitivity but variable specificity (82-100% when leishmaniasis cases were included); others using recombinant antigens or synthetic peptides are more specific than crude extracts from T. cruzi epimastigote forms, with sensitivity ranging from 75-100% (Caballero et al 2007).…”
Section: Why Does Cs Remain Positive After Drug Treatment and Cure Ofmentioning
confidence: 99%